(untitled) (Research, Society and Development, 2021)
This work presents the morphology of 16 medicinal species of Lamiales used in Alta Floresta, Mato Grosso, Brazil, as well comments about phytogeography, popular use in the municipality, the status of the species in the National Policy on Medicinal Plants and Phytotherapeutics, and examples of preclinical trials. The work was performed between March and September 2020, through botanical sample of the Lamiales species presented in the book " Plantas medicinais de Alta Floresta: com contribuição a etnobotânica", obtained in rural communities and urban neighborhoods in the municipality of Alta Floresta, State of Mato Grosso. The morphological study was carried out at the Laboratory of Plant Morphology, located at the University Campus of Alta Floresta, Universidade do Estado de Mato Grosso. In general, the species are native (56%) with wide distributions in Brazil. Most species have glandular trichomes (72%) on the leaves and/or flowers and have been shown to be efficient and/or promising (85.5%) in studies. However, only 37.5% of these studies were conducted by the Ministry of Health. None of the species are offered as a phytotherapeutic by the Unified Health System (SUS), although six are on the last National Report of Medicinal Plants of Interest published by SUS. Based on the information provided, it is evident that these species could be used in studies about new phytotherapeutics for SUS users.